Is DrEaMing (drinking, eating and mobilising) the dream?. (2nd August 2021) - Sahni, Arun
Abstract : The idea of patients drinking, eating and mobilising (DrEaMing) at 24 hours postoperatively is being used as a marker of functional recovery. This marker of recovery and quality is explored in this article.